Pengenalan Skrining Tumbuh Kembang Anak Usia Dini Berbasis Guru PAUD di TK Al Fath Desa Gondanglegi Kecamatan Prambon Kabupaten Nganjuk - Wijayanti, Endah Tri; Risnasari, Norma; Aizah, Siti (Universitas Nusantara PGRI Kediri, 2022)
PAUD teachers as a pionerr in detecting the children's growth and development. This programe is aim to improve the ability of PAUD teachers in monitoring growth and development of children. The participants of this programe were 9 teachers. The screening training programe was used the KPSP forms which was adapted from the Ministry of Health of Indonesia. This activity was implemented for 3 days using the lecture method, studio display, and role play. The result of this training programe is increasing of knowledge that measured by average score of pretest 45.11; posttest 83.33; skill score 79.89; and 2 children with delay results in aspects of socialization and independence. Screening activities need to be continuously programe in childhood institutions to prevent possibility of deviations in child development.